Virtual Screening And Molecular Docking Analysis For Predicting The Potential Cyclooxygenase-2 Inhibiting Drugs In The Treatment Of Cancer - EZHILARASAN .V; CHINNATHAMBI. V; JANARTHANAN .V; YAZHINI K.A; SRIDHAR .S (International Journal of Pharma and Bio Sciences, 2012)
Cyclooxygenase-2 is being treated as one of the chief anti-cancer targets for colorectal, lung, breast, prostate and head/neck cancer. The focus of this study is to discover new ligand molecules, which can be used as a potential drug against Cyclooxygenase-2. The structure of Cyclooxygenase-2 of Homo sapiens was modeled using “MODELLER”. The FDA approved and experimental level drugs are available in DrugBank3.0 database was screened against Cyclooxygenase-2 using the virtual screening facility offered by PYR-X0.8 software. Molecular docking studies were performed using AutoDock Wizard and the results were analyzed critically with the help of AutoDock tools 1.4.5. Virtual Screening and Molecular Docking Analysis revealed four molecules. Namely, N-cyclopropyl-4-methyl-3-[1-(2-methylphenyl) phthalazin-6-yl]benzamide, 6-Fluoro-2-(2’-Fluoro-1,1’-Biphenyl-4-Yl)-3-Methylquinoline-4-Carboxylic Acid, Eletriptan and Tamibarotene.